High Resolution Human Eye Tracking During Continuous Visual Search - Martin, Jacob G.; Davis, Charles E.; Riesenhuber, Maximilian; Thorpe, Simon J. (Frontiers in Human Neuroscience, 2018)
While several studies have shown human subjects’ impressive ability to detect faces in individual images in paced settings (Crouzet et al., 2010), we here report the details of an eye movement dataset in which subjects rapidly and continuously targeted single faces embedded in different scenes at rates approaching six face targets each second (including blinks and eye movement times). In this paper, we describe details of a large publicly available eye movement dataset of this new psychophysical paradigm (Martin et al., 2018). The paradigm produced high-resolution eye-tracking data from an experiment on continuous upright and inverted 3° sized face detection in both background and no-background conditions. The new “Zapping” paradigm allowed large amounts of trials to be completed in a short amount of time. For example, our three studies encompassed a total of 288,000 trials done in 72 separate experiments, and yet only took approximately 40 hours of recording for the three experimental cohorts. Each subject did 4000 trials split into eight blocks of 500 consecutive trials in one of the four different experimental conditions: {upright, inverted} × {scene, no scene}. For each condition, there are several covariates of interest, including: temporal eye positions sampled at 1250 hz, saccades, saccade reaction times, microsaccades, pupil dynamics, target luminances, and global contrasts.